Oral health-related quality of life and satisfaction in edentulous patients rehabilitated with implant-supported full dentures all-on-four concept: a systematic review - Gonçalves, Gabriela Sumie Yaguinuma [UNESP]; de Magalhães, Keith Murieli Ferreira [UNESP]; Rocha, Eduardo Passos [UNESP]; dos Santos, Paulo Henrique [UNESP]; Assunção, Wirley Gonçalves [UNESP] (Springer Nature, 2022)
Objective: Address oral health-related quality of life (OHRQoL) and patient satisfaction rehabilitated by the all-on-four concept as the primary outcome. Material and methods: A search was performed in the PubMed/MEDLINE, Web of Science, and Cochrane databases according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis criteria (PRISMA). The PICO question was used to address the following specific question: “What is the level of oral health-related quality of life and satisfaction in edentulous patients and with atrophic jaws who received dental implants for full-arch implant-supported restorations following the all-on-four in the mandible or maxilla?” Results: Eleven studies including 693 patients aged 55 to 71 years were selected. The shortest follow-up period was 3 months and the longest, 7 years. Regarding the OHRQoL assessment method and patient satisfaction, the oral health impact profile (OHIP) and the visual analog scale (VAS) were the most used. Conclusion: OHRQoL and satisfaction in patients whose rehabilitation was based on the all-on-four concept were high. However, the current evidence is still limited by the quality of the available studies, making long-term randomized studies necessary to establish the real effectiveness of this surgical-prosthetic approach. Clinical relevance: Carefully analyze the aspects related to satisfaction and oral health-related quality of life of rehabilitated patients with implant-supported total prostheses made according to the all-on-four concept, aiming to achieve success through procedures with greater predictability and less complexity, as these are directly associated with recovery oral health of edentulous individuals with less morbidity and minimized costs.
Keywords: All-on-four; Edentulous atrophic maxilla; Immediate loading; OHRQoL; Satisfaction; Tilted implants